DNA mismatch repair and CD133-marked cancer stem cells in colorectal carcinoma - Cheah, Phaik Leng; Li, Jing; Looi, Lai Meng; Teoh, Kean Hooi; Ong, Diana Bee Lan; Arends, Mark J. (PeerJ, 2018)
Background. Except for a few studies with contradictory observations, information is lacking on the possibility of association between DNA mismatch repair (MMR) status and the presence of cancer stem cells in colorectal carcinoma (CRC), two important aspects in colorectal carcinogenesis. Methods. Eighty (40 right-sided and 40 left-sided) formalin-fixed, paraffin-embedded primary CRC were immunohistochemically studied for CD133, a putative CRC stem cell marker, and MMR proteins MLH1, MSH2, MSH6 and PMS2. CD133 expression was semi-quantitated for proportion of tumor immunopositivity on a scale of 0-5 and staining intensity on a scale of 0-3 with a final score (units) being the product of proportion and intensity of tumor staining. The tumor was considered immunopositive only when the tumor demonstrated moderate to strong intensity of CD133 staining (a decision made after analysis of CD133 expression in normal colon). Deficient MMR (dMMR) was interpreted as unequivocal loss of tumor nuclear staining for any MMR protein despite immunoreactivity in the internal positive controls. Results. CD133 was expressed in 36 (90.0%) left-sided and 28 (70.0%) right-sided tumors (p < 0:05) and CD133 score was significantly higher in left- (mean ± SD D 9.6 ± 5.3 units) compared with right-sided tumors (mean ± SD D 6.8 ± 5.6 units) p < 0:05).dMMRwas noted in 14 (35%) right-sided and no (0%) left-sided CRC. When stratified according to MMR status, dMMR cases showed a lower frequency of CD133 expression (42.9%) and CD133 score (mean ± SD D 2.5 ± 3.6 units) compared with pMMR tumors on the right (frequency D 84.6%; mean score ± SD D 9.2 ± 5.0 units) as well as pMMR tumors on the left (frequency D 90.0%; mean score ± SD D 9.6 ± 5.3 units) (p < 0:05). Interestingly, frequencies of CD133 immunoreactivity and CD133 scores did not differ between pMMR CRC on the right versus the left (p > 0:05). Conclusion. Proficient MMR correlated with high levels of CD133-marked putative cancer stem cells in both right- and left-sided tumors, whereas significantly lower levels of CD133-marked putative cancer stem cells were associated with deficientMMRstatus in colorectal carcinomas found on the right.